The EULAR–OMERACT rheumatoid arthritis MRI reference image atlas: the wrist joint. (12th January 2005) - Ejbjerg, B; McQueen, F; Lassere, M; Haavardsholm, E; Conaghan, P; O'Connor, P; Bird, P; Peterfy, C; Edmonds, J; Szkudlarek, M; Genant, H; Emery, P; et al.
Abstract : This paper presents the wrist joint MR images of the EULAR–OMERACT rheumatoid arthritis MRI reference image atlas. Reference images for scoring synovitis, bone oedema, and bone erosions according to the OMERACT RA MRI scoring (RAMRIS) system are provided. All grades (0–3) of synovitis are illustrated in each of the three wrist joint areas defined in the scoring system—that is, the distal radioulnar joint, the radiocarpal joint, and the intercarpal-carpometacarpal joints. For reasons of feasibility, examples of bone abnormalities are limited to five selected bones: the radius, scaphoid, lunate, capitate, and a metacarpal base. In these bones, grades 0–3 of bone oedema are illustrated, and for bone erosion, grades 0–3 and examples of higher grades are presented. The presented reference images can be used to guide scoring of wrist joints according to the OMERACT RA MRI scoring system.